Conversion of Biomass of Bagasse to Syngas Through Downdraft Gasification (Jurnal Bahan Alam Terbarukan, 2018)
National energy demand has been fulfilled by non-renewable energy sources, such as natural gas, petroleum, coal and so on. However, non-renewable energy reserves deplete increasingly which can cause an energy crisis. Conversion of biomass into energy becomes one of the solutions to overcome it. Indonesia has an enormous biomass potential especially from sugarcane plantation. Sugarcane plantations produce waste of bagasse abundantly. Commonly bagasse is utilized as energy source by conventional combustion.Â  This research studies the utilization of bagasse as energy source by gasification technology to produce gas fuel. The gasification model used in this research is downdraft gasifier equipped with cyclone to separate gas with solid or liquid gasification products. The result has shownÂ  that gasification of bagasse has produced flammable syngas. The increase of bagasse weight increases the amount of syngas of gasification process. Carbon monoxide is the greatest content of syngas, while a few amount of H2, CH4 are also detected. Bagasse through gasification process is very potential source of alternative energy, since it is derived from waste and a cheap material.